Acylpeptide Hydrolase Inhibition as Targeted Strategy to Induce Proteasomal Down-Regulation - Palmieri, Gianna; Bergamo, Paolo; Luini, Alberto; Ruvo, Menotti; Gogliettino, Marta; Langella, Emma; Saviano, Michele; Hegde, Ramanath N.; Sandomenico, Annamaria; Rossi, Mose (PLOS ONE, 2011)
Acylpeptide hydrolase (APEH), one of the four members of the prolyl oligopeptidase class, catalyses the removal of N-acylated amino acids from acetylated peptides and it has been postulated to play a key role in protein degradation machinery. Disruption of protein turnover has been established as an effective strategy to down-regulate the ubiquitin-proteasome system (UPS) and as a promising approach in anticancer therapy. Here, we illustrate a new pathway modulating UPS and proteasome activity through inhibition of APEH. To find novel molecules able to down-regulate APEH activity, we screened a set of synthetic peptides, reproducing the reactive-site loop of a known archaeal inhibitor of APEH (SsCEI), and the conjugated linoleic acid (CLA) isomers. A 12-mer SsCEI peptide and the trans10-cis12 isomer of CLA, were identified as specific APEH inhibitors and their effects on cell-based assays were paralleled by a dose-dependent reduction of proteasome activity and the activation of the pro-apoptotic caspase cascade. Moreover, cell treatment with the individual compounds increased the cytoplasm levels of several classic hallmarks of proteasome inhibition, such as NFkappaB, p21, and misfolded or polyubiquitinylated proteins, and additive effects were observed in cells exposed to a combination of both inhibitors without any cytotoxicity. Remarkably, transfection of human bronchial epithelial cells with APEH siRNA, promoted a marked accumulation of a mutant of the cystic fibrosis transmembrane conductance regulator (CFTR), herein used as a model of misfolded protein typically degraded by UPS. Finally, molecular modeling studies, to gain insights into the APEH inhibition by the trans10-cis12 CLA isomer, were performed. Our study supports a previously unrecognized role of APEH as a negative effector of proteasome activity by an unknown mechanism and opens new perspectives for the development of strategies aimed at modulation of cancer progression.